Psychostimulant-Induced Fos Protein Expression in the Thalamic Paraventricular Nucleus - Deutch, Ariel Y. (J Neurosci, 1998)
Lesions of glutamatergic afferents to the nucleus accumbens have been reported to block psychostimulant-induced behavioral sensitization. However, thalamic glutamatergic projections to the nucleus accumbens have received little attention in the context of psychostimulant actions. We examined the effects of acute amphetamine and cocaine administration on expression of Fos protein in the thalamic paraventricular nucleus (PVT), which provides glutamatergic inputs to the nucleus accumbens and also receives dopaminergic afferents. Immunoblot and immunohistochemical studies revealed that both psychostimulants dose-dependently increased PVT Fos expression. PVT neurons retrogradely labeled from the nucleus accumbens were among the PVT cells that showed a Fos response to amphetamine. D(2)family dopamine agonists, including low doses of the D(3)-preferring agonist 7-OH-DPAT, increased the numbers of Fos-like-immunoreactive neurons in the PVT. Conversely, the effects of cocaine and amphetamine on PVT Fos expression were blocked by pretreatment with the dopamine D(2/3) antagonist raclopride. Because PVT neurons express D(3) but not other dopamine receptor transcripts, it appears that psychostimulants induce Fos in PVT neurons through a D(3) dopamine receptor. We suggest that the PVT may be an important part of an extended circuit subserving both the arousing properties and reinforcing aspects of psychostimulants.